Does orthodontic postgraduate education influence the choice of orthodontic treatment? - Saccomanno, Sabina; Saran, Stefano; Petricca, Maria Teresa; Caramaschi, Elena; Ferrante, Laura; Inchingolo, Francesco; Inchingolo, Angelo Michele; Palermo, Andrea; Dipalma, Gianna; Inchingolo, Alessio Danilo (Frontiers in Dental Medicine, 2025)
AimThe purpose of this study is to understand how the training of a clinician influences his or her therapeutic choices in the orthodontic field.Materials and methodsAn anonymized questionnaire was submitted to 317 Italian dentists to ask them about their training and what orthodontic therapies they perform. The answers were processed by statistical analysis.Results221 of 314 respondents (70.3%) had an orthodontic postgraduate education and 93 subjects did not (29.7%). Out of the whole sample, 242 clinicians use functional therapy (i.e., Frankel, Bionator or Andresen), but while 133 of them, after functional therapy, apply both fixed orthodontic appliances (i.e., Straight wire, Tweed or Rickets) and aligners, 79 use only fixed oral appliances, and 19 dentists use only an aligner. The application of a lingual technique is perfectly independent from having an orthodontic postgraduate education or not.ConclusionDifferences were found between dentists with an orthodontic postgraduate education and dentists without it. Most dentists in Italy pursued a postgraduate education. In addition, most orthodontists are dedicated exclusively to orthodontics in their office, while dentists who don't have an orthodontic postgraduate education do not practice orthodontics exclusively in their offices. It is possible to conclude that pursuing a specialization in orthodontics determines advantages for both practitioners and patients: it gives orthodontists those extra skills to customize a diagnosis and daily treatments in a more precise and innovative way, using a wider variety of therapeutic options and relying more on teamwork, for complementary solutions. These additional skills usually increase a treatment's success and decrease complications, which, first and foremost, benefit the patients.